Photopyroelectric technique for the measurement of optical properties of pure liquids (Superficies y Vacío, 2023)
Photopyroelectric technique, in the transmission configuration, was shown adequate for the measurement of the optical properties of pure liquids. The analytical scheme involves the scanning of the photopyroelectric signal as a function of the sample thickness. Optical absorption coefficients, at four wavelengths in the near infrared region (904 nm, 980 nm, 1310 nm, and 1550 nm), were measured for eight pure substances, distilled water and glycerol, among them. Strong optical absorption was obtained, particularly for pure liquids with a hydroxyl group in their molecular structure. In order to figure out about the influence of this chemical group on optical properties as function of the size of the molecule, optical absorption coefficient for a series of linear alcohols at 1550 nm was also measured.